Synergy enhancement for sustainable solid waste management service in selected municipalities of coastal tourist destinations, Ghana - Abena Ayepah Atta-Gyan; Surasak Jotaworn; Supit Boonlab (Discover Sustainability)
Abstract Municipal solid waste (MSWM) service in Ghana’s coastal tourist zone is under pressure due to growing tourism, institutional constraints, and fast urbanization. Environmental deterioration, ineffective waste management, and public health issues are the results of these difficulties. Through integrating involvement from the community, private sector, and local government efforts, this study investigates synergistic opportunities to improve MSWM’s sustainability. This study applied a mixed-methods approach that includes 367 survey responses and key informant interviews across three municipalities in Ghana’s Central Region: Gomoa West, Mfantsiman, and Effutu. It was based on the frameworks of sustainable tourism and environmental governance. The results showed that, particularly during the highest-volume travel seasons, there were infrastructure gaps, low rates of household waste sorting (34%) and general dissatisfaction with the waste services currently in place. According to statistical analyses, sorting behavior was positively influenced by education, whereas environmentally conscious practices are negatively correlated with higher consumer orientation. Decentralized waste policies existed, but public participation was low and enforcement was weak. In response to the study, there are four main ways to improve synergy: (1) community-based recycling and sorting programs; (2) behavioral change brought about by education; (3) reinvesting tourism-related income into regional waste systems; and (4) forming public-private partnerships to improve logistics and service delivery. By offering a localized synergy framework designed for municipalities with high tourism in developing countries, this study contributes an existing body of literature also the policymakers with useful information for achieving sustainable waste governance.